The Depletion Mechanism Actuates Bacterial Aggregation by Exopolysaccharides and Determines Species Distribution & Composition in Bacterial Aggregates - Secor, Patrick R.; Michaels, Lia A.; Bublitz, DeAnna C.; Jennings, Laura K.; Singh, Pradeep K. (Frontiers in Cellular and Infection Microbiology, 2022)
Bacteria in natural environments and infections are often found in cell aggregates suspended in polymer-rich solutions, and aggregation can promote bacterial survival and stress resistance. One aggregation mechanism, called depletion aggregation, is driven by physical forces between bacteria and high concentrations of polymers in the environment rather than bacterial activity per se. As such, bacteria aggregated by the depletion mechanism will disperse when polymer concentrations fall unless other adhesion mechanisms supervene. Here we investigated whether the depletion mechanism can actuate the aggregating effects of P. aeruginosa exopolysaccharides for suspended (i.e. not surface attached) bacteria, and how depletion affects bacterial inter-species interactions. We found that cells overexpressing the exopolysaccharides Pel and Psl remained aggregated after short periods of depletion aggregation whereas wild-type and mucoid P. aeruginosa did not. In co-culture, depletion aggregation had contrasting effects on P. aeruginosa’s interactions with coccus- and rod-shaped bacteria. Depletion caused S. aureus (cocci) and P. aeruginosa (rods) to segregate from each other and S. aureus to resist secreted P. aeruginosa antimicrobial factors resulting in species co-existence. In contrast, depletion aggregation caused P. aeruginosa and Burkholderia sp. (both rods) to intermix, enhancing type VI secretion inhibition of Burkholderia by P. aeruginosa, leading to P. aeruginosa dominance. These results show that in addition to being a primary cause of aggregation in polymer-rich suspensions, physical forces inherent to the depletion mechanism can promote aggregation by some self-produced exopolysaccharides and determine species distribution and composition of bacterial communities.